Can agricultural water rights trading promote intensive and economical utilization of water resources in China based on the difference-in-differences model? - Rong, Lili; Cheng, Xin (Frontiers in Environmental Science, 2024)
Improving the level of intensive and economical utilization of water resources is an important measure related to water resources security and food security. Based on China's provincial panel data from 2015 to 2021, this study uses a difference-in difference(DID) model to examine the effects of the agricultural water rights trading on intensive and economical utilization of water resources. We find that agricultural water rights trading can significantly promote the intensive and economical utilization of water resources at 1% level, and after a series of robustness tests, the result is still valid. Further analysis indicates that agricultural water rights trading can promote intensive and economical utilization of water resources by significantly reducing agricultural water consumption at 1% level and reducing the proportion of agricultural water consumption at 5% level to optimize water use structure. Moreover, in the regions with scarce water resources, strong constraints on water resources, more farmland water conservancy construction and higher economic development level, the promotion effect of agricultural water rights trading on the intensive and economical use of water resources is more significant. This study provides evidence for evaluating the effects of China's agricultural water rights trading policy and offers new ideas and experiences for improving China's water resource utilization efficiency.The marginal contribution of this article may have the following three points: First, this paper clearly distinguishes the intensive conservation of water resources, constructs the evaluation index system respectively, and supplements the existing literature on the measurement of the intensive and economical utilization of water resources. Second, this paper analyzes the transmission path of agricultural water rights trading to improve the level of intensive and economical utilization of water resources, it enriches the research of related transmission mechanism. Third, the heterogeneity of the influence of different regional condition on the level of intensive and economical utilization of water resources is deeply discussed, in order to improve the relevant policies.